FEMALE CIRCUMCISION: BETWEEN MYTH AND LEGITIMATE DOCTRINAL ISLAM - Mesraini, Mesraini (Jurnal Syariah, 2010)
Circumcision on female has sociologically been practiced since long time ago. It is believed to be done for certain purposes. One of the intentions is that it is as an evidence of sacrifice of the circumcised person to get close to God. In the last decades, the demand for ignoring this practice on female by various circles often springs. Reason being is that the practice is accused of inflicting female herself. Moreover, it is regarded as a practice that destroys the rights of female reproduction and that of female sexual enjoyment and satisfaction. Commonly, female circumcision is done by cutting clitoris and throwing the minor and major labia. This practice of circumcision continues based on the myths that spread so commonly among people. This article aims to conduct a research on female circumcision in the perspective of Islamic law. According to Islamic doctrine, female circumcision is legal by Islamic law. By adopting the methodology of syar‘a man qablana (the law before us) and theory of maqasid al-syari‘ah (the purposes of Islamic law) and some other legitimate Quranic verses, circumcision becomes an important practice. Again, the famous female circumcision practice is evidently not parallel with the way recommended by Islam.